SOEP scales manual (updated for SOEP-Core v32.1) - David Richter; Julia Rohrer; Maria Metzing; Wiebke Nestler; Michael Weinhardt; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This manual briefly describes the theoretical background and development of all of the scales used in the Socio-Economic Panel (SOEP) study. It also provides the relevant citations as well as the items belonging to the scales and the answer format, including the verbal anchors. The unique value of this manual lies in the presentation of each scale in the form of easy-to-understand tables listing variable names of the items in the scale in a wave-specific dataset (labels). This allows the individual items to be found and aggregated quickly. In addition, the tables in this manual include mean values (M), standard deviations (SD), corrected item-total correlations (CITC), and information as to whether the item has to be recoded before aggregation (R). The number of valid cases in the particular survey years, as well as two measures of reliability, the internal consistency (Cronbach's Alpha) and test-retest correlations (if available), are also reported.
Keywords: 330